The Radiographer's multidisciplinary team role in theatre scenarios. Issue 2 (May 2015) - Williams, H.; Widdowfield, M.; Cosson, P.
Abstract Background Radiographers work in multidisciplinary teams (MDTs) to image intra-operatively using ionising radiation. The radiographer is responsible according to IR(ME)ER (2000) and IRR(99) regulations for advocating patient and theatre personnel safety. A comprehensive literature search revealed limited studies analysing the radiographer's experiences of utilising power to influence MDTs. Therefore the aim of the study was to explore the power relationships within different MDT scenarios. Method A qualitative approach was adopted consisting of interviews exploring radiographers' experiences as 1) established Cardiology team members and 2) transient members of Orthopaedic teams. French and Raven's power bases were used as an a priori framework. Ethical approval was obtained prior to commencement. Sampling was purposive, following gatekeeper permission, and subsequent participation was voluntary. Thematic content analysis was undertaken following data collection. Findings and discussion Perpetration of Legitimate Power was more frequently attempted in transient teams. However, there were more successful descriptions in established teams. Expert Power was reciprocated successfully in established teams but was context dependent in transient teams. Referent power was well used by participants, although the transient nature of teams did affect this. Job satisfaction was expressed by both groups, although evidence presented was more comprehensive in established teams. Conclusion The social bases of power at play within two MDTs have been examined. It is unclear to what extent the team specialism has a role in the differences identified. Radiographers working in established teams may have greater job satisfaction and perpetrate power bases more effectively than radiographers serving in transient teams.